John R. Commons' Criticism of Wicksell's Theory of Interest: Focusing on the Influence of R. G. Hawtrey. Issue 4 (1st October 2020) - Uni, Hiroyuki
Abstract: John R. Commons is one of the founders of the American institutional school. In recent years, two compiled manuscripts of his main book, Institutional Economics, were discovered in Japan and in the United States. One is a manuscript written in 1927 found at the Kyoto Prefectural Library, and the other is a manuscript dated 1928–29 found at The United States Department of Agriculture's National Agricultural Library. Using these manuscripts, this article examines formation process of Commons' institutional theory of interest. In particular, the influence of R. G. Hawtrey on Commons' theory is explained. Commons depended heavily on Hawtrey's theory in order to overcome some limitations included in Wicksell's theory, in the section of Institutional Economics titled "A World Pay Community." This is clarified mainly by comparing it with a section of the manuscript with the same title, which did not refer to Hawtrey.